Physicochemical and Microbiological Analysis of Steel Plant Effluents of Visakhapatnam, Andhra Pradesh - Elizabeth, K.M.; Gayatri, B.; Tulasi Kumari, G.; Vimala, Y. (Asian Journal of Chemistry, 2010)
The physicochemical and microbiological analysis of Visakhapatnam steel plant effluents, both treated and untreated was performed. The physical parameters tested were pH, conductivity, turbidity and temperature; among them, conductivity was beyond the permissible limit before and after the treatment of the effluent. Turbidity was very high in the untreated effluent which was reduced to below the normal limit. The microbiological analysis such as coliform counts and total plate counts had exceeded the normal limit. The total hardness, Ca hardness and Mg hardness, chlorides, total solids, total dissolved solids and ammonia contents were above the permissible limit in both the effluents indicating that the effluents were highly polluted. The bioremediation studies with viable, killed and immobilized non-pathogenic bacteria revealed the fact that there was 76.9%, 97.1% and 95.7% removal of ammonia respectively from treated and untreated effluents. There was 500 mg/L of phenol in untreated effluent which was reduced to < 1 mg/L in treated effluent. Bioremediation could also remove oil and grease to some extent. These results indicate that the treated and untreated effluents of this industry were highly contaminated and bioremediation with non-pathogenic microorganisms was a successful measure of treatment.